Fungus mediated synthesis of biomedically important cerium oxide nanoparticles - Khan, Shadab Ali; Ahmad, Absar (Materials Research Bulletin, 2013)
Nanomaterials can be synthesized by chemical, physical and the more recently discovered biological routes. The biological routes are advantageous over the chemical and physical ones as unlike these, the biological synthesis protocols occur at ambient conditions, are cheap, non-toxic and eco-friendly. Although purely biological and bioinspired methods for the synthesis of nanomaterials are environmentally benign and energy conserving processes, their true potential has not been explored yet and attempts are being made to extend the formation of technologically important nanoparticles using microorganisms like fungi. Though there have been reports on the biosynthesis of oxide nanoparticles by our group in the past, no attempts have been made to employ fungi for the synthesis of nanoparticles of rare earth metals or lanthanides. Here we report for the first time, the bin-inspired synthesis of biomedically important cerium oxide (CeO2) nanoparticles using the thermophilic fungus Humicola sp. The fungus Humicola sp. when exposed to aqueous solutions of oxide precursor cerium (III) nitrate hexahydrate (CeN3O9 center dot 6H(2)O) results in the extracellular formation of CeO2 nanoparticles containing Ce (III) and Ce (IV) mixed oxidation states, confirmed by X-ray Photoemission Spectroscopy (XPS). The formed nanoparticles are naturally capped by proteins secreted by the fungus and thus do not agglomerate, are highly stable, water dispersible and are highly fluorescent as well. The biosynthesized nanoparticles were characterized by UV-vis spectroscopy, Photoluminescence spectroscopy (PL), Transmission Electron Microscopy (TEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and X-ray Photoemission Spectroscopy (XPS). (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Electron microscopy; Nanostuctures; Optical properties; Oxides; X-ray diffraction

Fungus-mediated preferential bioleaching of waste material such as fly - ash as a means of producing extracellular, protein capped, fluorescent and water soluble silica nanoparticles - Khan, Shadab Ali; Uddin, Imran; Moeez, Sana; Ahmad, Absar (PLoS One, 2014)
In this paper, we for the first time show the ability of the mesophilic fungus Fusarium oxysporum in the bioleaching of waste material such as Fly-ash for the extracellular production of highly crystalline and highly stable, protein capped, fluorescent and water soluble silica nanoparticles at ambient conditions. When the fungus Fusarium oxysporum is exposed to Fly-ash, it is capable of selectively leaching out silica nanoparticles of quasi-spherical morphology within 24 h of reaction. These silica nanoparticles have been completely characterized by UV-vis spectroscopy, Photoluminescence (PL), Transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Energy dispersive analysis of Xrays (EDAX).